Evaluasi Penerapan Community Based Tourism (CBT) - Diana, Diana; Setiawan, Avi Budi (Efficient: Indonesian Journal of Development Economics, 2021)
Tourism is one of the growing sectors in Indonesia. One of the cities in Central Java that has both natural and artificial tourism potential is Pekalongan City. Nature tourism in Pekalongan City is still lacking in community involvement. The purpose of this study was to analyze the extent to which the existence and implementation as well as the obstacles in the implementation of Community Based Tourism (CBT) in these tours. Methods of data collection using interviews, observation, and documentation. The data analysis technique in this study used a narrative descriptive technique. The results showed that the community has been involved in tourism management but it is still not in accordance with the expected target. A good Community Based Tourism is the Pasir Kencana beach which is seen from the activity of a good tourism awareness group (Pokdarwis). Constraints in community-based tourism management in tourism are natural factors as well as factors from human resources. Pariwisata merupakan salah satu sektor yang sedang berkembang di Indonesia. Salah satu Kota di Jawa Tengah yang memiliki potensi wisata baik alam dan buatan adalah Kota Pekalongan. Wisata alam di Kota Pekalongan masih kurang dalam keterlibatan masyarakatnya. Tujuan dari penelitian ini adalah untuk menganalisis sejauh mana eksistensi dan implementasi serta kendala dalam penerapan Community Based Tourism (CBT) di wisata tersebut. Metode pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data pada penelitian ini menggunakan teknik deskriptif naratif. Hasil penelitian menunjukkan bahwa masyarakat sudah ikut terlibat dalam pengelolaan pariwisata namun masih belum sesuai dengan target yang diharapkan. Community Based Tourism yang baik adalah pantai pasir kencana dimana dilihat dari keaktifan kelompok sadar wisata (Pokdarwis) yang baik. Kendala dalam pengelolaan pariwisata berbasis masyarakat di wisata tersebut adalah faktor alam dan juga faktor dari sumber daya manusianya.